Gang Involvement in "Rock" Cocaine Trafficking in Los Angeles, 1984-1985 - Klein, Malcolm W. ([Verlag nicht ermittelbar], 1991)
The purpose of this data collection was to investigate the possible increase in gang involvement within cocaine and "rock" cocaine trafficking. Investigators also examined the relationships among gangs, cocaine trafficking, and increasing levels of violence. They attempted to determine the effects of increased gang involvement in cocaine distribution in terms of the location of an incident, the demographic profiles of suspects, and the level of firearm use. They also looked at issues such as whether the connection between gangs and cocaine trafficking yielded more drug-related violence, how the connection between gangs and cocaine trafficking affected police investigative processes such as intra-organizational communication and the use of special enforcement technologies, what kinds of working relationships were established between narcotics units and gang control units, and what the characteristics were of the rock trafficking and rock house technologies of the dealers. Part 1 (Sales Arrest Incident Data File) contains data for the cocaine sales arrest incidents. Part 2 (Single Incident Participant Data File) contains data for participants of the cocaine sales arrest incidents. Part 3 (Single Incident Participant Prior Arrest Data File) contains data for the prior arrests of the participants in the cocaine arrest incidents. Part 4 (Multiple Event Incident Data File) contains data for multiple event incidents. Part 5 (Multiple Event Arrest Incident Data File) contains data for arrest events in the multiple event incidents. Part 6 (Multiple Event Incident Participant Data File) contains data for the participants of the arrest events. Part 7 (Multiple Event Incident Prior Arrest Data File) contains data for the prior arrest history of the multiple event participants. Part 8 (Homicide Incident Data File) contains data for homicide incidents. Part 9 (Homicide Incident Suspect/Victim Data File) contains data for the suspects and victims of the homicide incidents. Major variables characterizing the various units of observation include evidence of gang involvement, presence of drugs, presence of a rock house, presence of firearms or other weapons, presence of violence, amount of cash taken as evidence, prior arrests, and law enforcement techniques.